2017
DOI: 10.1016/j.ipej.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of ICD indication at the time of replacement in patients with initial implant for primary prevention indication: Effect on subsequent ICD therapies

Abstract: BackgroundIndication to implantable cardioverter defibrillator (ICD) for primary prevention of sudden death relies on left ventricular ejection fraction (LVEF). We measured the proportion of patients in whom indication to ICD persisted at the time of generator replacement (GR) and searched for predictors of appropriate therapies after GR.MethodsWe identified all consecutive patients who had received an ICD at our hospital, for LVEF ≤35% and no previous arrhythmias or unexplained syncope. Then, we included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A total of 31,640 patients from 20 studies (14 retrospective and 6 prospective registries) were included in our meta-analysis (Figure 1) with a mean ± standard deviation age of 65.6 ± 4.7 years (mean age range, 57-76 years) and follow-up period of 3.1 ± 1.5 years. 2,6,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The critical appraisal performed using the Newcastle-Ottawa scale revealed that the quality of studies was good (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 31,640 patients from 20 studies (14 retrospective and 6 prospective registries) were included in our meta-analysis (Figure 1) with a mean ± standard deviation age of 65.6 ± 4.7 years (mean age range, 57-76 years) and follow-up period of 3.1 ± 1.5 years. 2,6,10,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The critical appraisal performed using the Newcastle-Ottawa scale revealed that the quality of studies was good (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The 6 studies [12][13][14][15][16][17] finally included were retrieved in just the last 4 years of literature review, 3 were published in 2016, 2 in 2014, 1 in 2017. Study design was observational retrospective in all cases.…”
Section: Study Populationmentioning
confidence: 99%
“…Study design was observational retrospective in all cases. One study only reported adjustment for confounding [16]. A total of 733 patients were enrolled in our analysis, 255 in patients without persistent ICD indication and 478 in patients with persistent ICD indication.…”
Section: Study Populationmentioning
confidence: 99%
“…In this manuscript, Dell'era et al. [1] select a group of patients with a primary prevention indication for an ICD who then go on to get a generator exchange, and examine the risk of future arrhythmic events in those with persistent indications for ICD at the time of GE, and those without ongoing indications. In the group of patients who have received prior therapy from their device, the decision to perform a generator exchange is straightforward-prior history of arrhythmic events is the strongest predictor of future arrhythmic events.…”
mentioning
confidence: 99%